Langerhans Cells Histiocytosis: Features of Clinical and Laboratory Manifestations and Course of the Disease - O.I. Dorosh; I.P. Tsymbalyuk-Voloshyn; R.S. Polishchuk; L.Ya. Dubey; O.I. Vorobel; O.I. Kozlova; O.O. Troyanovska; O.I. Stepanyuk; L.L. Skoropad; N.I. Kitsera; L.P. Seredych; A.M. Mykh; et al. (Zaslavsky O.Yu., 2014)
The aim of the research. To specify the features of clinical symptoms, course of the disease and the efficacy of treatment for Langerhans cells histiocytosis (LCH) in children. Methods of the Study. Clinacal, haemotological, biochemical, histological, immunohistochemical, radiological ones. Results of the Study. An analysis of 25 cases of LCH in children was presented. Monosystem LCH most often affects the skeletal system. Multisystem LCH is characterized by diversity of clinical manifestations, more severe course and high risk of death. One third of patients with multisystem LCH are infants. In children with monosystem LCH we observed complete clinical response to first-line therapy. At the same time, complete response to polychemotherapy is observed only in 30 % of children with multisystem LCH. Prognosis of the disease depends on the initial affection of risk organs (bone marrow, liver, lungs, spleen), their dysfunction and the child's age at the time of diagnosis. Process reactivation in children with multisystem LCH occurs in the first 12 months from the onset of the disease.